Financial Markets BRICS: The Analysis of Competitive Advantages - NOVIKOV, Alexander Vladimirovich; NOVIKOVA, Irina Yakovlevna (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
Analyzing the present range of economic and political inter-state cooperation in the world, it may be noticed that foundation of their alliances and associations based both on the principles of equality and supremacy of a main partner. One of such equal associations is the treaty among Brazil, Russia, India, China, and South Africa known as the BRICS. The article reveals the financial development strategy of the BRICS. It is researched resource potential of the BRICs as a basis of financial development. Suggested three directions forming a strategy of financial development of BRICS. Identified competitive advantages of the BRICS in the creation of a favorable institutional and macroeconomic stability, improve market sophistication and world financial centers. The results obtained can be the basis for the development of specific activities on the formation of the strategy of the financial development of the BRICS with the positions of their competitiveness.